Composition of Phenolics and Proteins of Theabrownin from Liupao Tea - WANG Yinzhu, TENG Jianwen, HUANG Li, XIA Ning, WEI Baoyao (Shipin Kexue)
In this study, theabrownin from Liupao tea was extracted and separated into extractable (FTB) and non-extractable (BTB) fractions using methanol. The composition of the two fractions was analyzed by Fourier transform infrared (FTIR) spectroscopy, sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE), Western blot, and ultra-high performance liquid chromatography-high resolution mass spectrometry (UPLC-HRMS). The study found that the theabrownin was a polyhydroxyl aromatic compound complexed with nitrogen compounds, including proteins, amino acids, and peptides. Electrophoresis showed two protein bands with molecular masses ranging from 63 to 75 kDa, which were generally diffuse long strip-shaped and may be modified by polyphenols and other substances. Non-targeted metabolomics identified 297 compounds. A total of 137 significantly differential compounds between FTB and BTB were selected using the cutoff of fold change (FC) > 2 or FC < 0.5 and P < 0.05, the major ones being phenolics (37). Principal component analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA) revealed that catechin, 2,3-dihydroxybenzoic acid, gallic acid, 4-hydroxycoumarin, and caffeic acid could be used to discriminate between FTB and BTB and may be the major non-extractable phenolics of theabrownin. This study contributes to the understanding of protein-polyphenol complexes in dark tea and encourages further research of the composition and functional activity of theabrownin in dark tea.